Reportes latinoamericanos sobre utilidad clínica diagnóstica de pruebas inmunológicas e histológicas en enfermedades del tiroides - Garzón Salazar, Karen Verónica (2022)
ABSTRACT: Thyroid diseases are frequent in Latin America, so laboratory diagnosis is of great importance, immunological tests detect anti-thyroid antibodies by immunoassays, while histological tests by fine needle puncture (FNAP), so the objective was to analyze the clinical diagnostic utility of immunological and histological tests in thyroid diseases. The research was developed through a descriptive study of non-experimental documentary design, cross-sectional and retrospective type, 112 bibliographic reviews of different scientific bases were carried out: From the bibliographic analysis it was found that the Latin American countries that carried out the greatest amount of research on the diagnosis of cancer were Cuba and Colombia; on the other hand, for the diagnosis of autoimmune diseases, the greatest amount of research was carried out in Mexico; in relation to autoimmune diseases and thyroid neoplasia, they occur more frequently in the female gender; On the other hand, in the quantification techniques, the most used immunoassay was chemiluminescence (50 %) which quantifies minimum concentrations of antithyroid antibodies due to its greater sensitivity, while among the histological tests the most used is the fine needle puncture (FNA) thanks to its specificity (85 %) and sensitivity (78 %) helps to differentiate benign or malignant pathologies. It is concluded that immunological and histological tests are of clinical diagnostic utility in Latin America in autoimmune thyroid diseases and cancer, because both have adequate sensitivity and specificity. Key words: antibodies, thyroid neoplasms, immunoassays.